Confidence Interval-Based Estimation of Relevance on Women’s Driving Ability and Its Association towards Road Environment - I. H. Abu Samah; I. M. Abd Rashid; A. S. Shamsudin; U. N. Saraih; N. S. A. Rahim (Journal of the Society of Automotive Engineers Malaysia, 2022)
The perception of the road environment is depending on the people, system, structure, and activities. A good perception of the road environment is important because it would be a symbol that our country possesses a good infrastructure. Meanwhile, apart from making the road environment sustainable, road users also play a greater role in determining the perception of the road environment. Women's ability plays a part in determining a sustainable road environment because the consequences, actions, and interventions outcome based on women's events may lead to the formulation of road systems and regulations. Therefore, determining women's ability towards the perception of road environment is very important. CIBER techniques were used to determine the behavior and the predicted outcome of the perception of the road environment. Results indicate that the association of the left and right panels showed that 33% of the variance in road environment was explained by the women's ability (R2 = 0.33). Each ability depicted in the visual plot explains differently women’s reactions towards the road environment. This research highlighted the impact of understanding women's ability and their responses in handling the situation on the road environment.